Christianity and human rights an introduction - Witte, John, 1959-; Alexander, Frank S., 1952- (Cambridge ; New York : Cambridge University Press, 2010)
"Combining Jewish, Greek, and Roman teachings with the radical new teachings of Christ and St. Paul, Christianity helped to cultivate the cardinal ideas of dignity, equality, liberty and democracy that ground the modern human rights paradigm. Christianity also helped shape the law of public, private, penal, and procedural rights that anchor modern legal systems in the West and beyond. This collection of essays explores these Christian contributions to human rights through the perspectives of jurisprudence, theology, philosophy and history, and Christian contributions to the special rights claims of women, children, nature and the environment. The authors also address the church's own problems and failings with maintaining human rights ideals. With contributions from leading scholars, including a foreword by Archbishop Desmond Tutu, this book provides an authoritative treatment of how Christianity shaped human rights in the past, and how Christianity and human rights continue to challenge each other in modern times"--
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Human rights -- Religious aspects -- Christianity; Christianity -- Influence; Human rights -- History; RELIGION / Ethics; Electronic books; RELIGION / Christianity / General